Coping with drought and food insecurity in Ethiopia - Webb, Patrick (Wiley, 1993)
In this article I examine the impact of drought on farm households in Ethiopia and their response to crisis conditions. I ask whether every household in a community is equally affected by drought and what households do to mitigate the effects of drought and associated food insecurity. Information on production, income and food consumption is disaggregated by agroecological zone (highland and lowland), and by socioeconomic strata (relatively wealthy versus poor). Such detailed analysis permits an improved understanding of why the poor are much more vulnerable than the wealthy to drought and associated famines and why they need to be more effectively targeted by relief and development interventions. In a world of limited public resources for crisis intervention, such understanding is crucial to the design of improved policies and projects for reaching people most at risk.